(untitled) (Harmoni, 2012)
The diversity of races, cultures, customs and religions of the people in an area, could lead to a conflict in the related area. This could happen also in the Province of West Sumatra. Such assumption underlies the feasibility of the study on religious harmony in the area. From the results of a case study with a qualitative method that raises the issue of subject matter ΓÇ£how is the religious people harmony in West SumatraΓÇ¥, revealed several things, such as: the conflicts occurred among religious people in some areas with various backgrounds; the presence of the exclusivity attitude and various schools of religious understanding, excessive ethnic and religious sentiments and the establishment of the worship house which does not pay attention on the regulations can lead to a conflict among religious communities; meanwhile, the cultures and local wisdoms of Minang society which still exist in society, the cultural assimilation, as well as proactive role of the local government are the integrative potency in improving the harmony in West Sumatra.